2021
DOI: 10.1016/j.nlm.2021.107382
|View full text |Cite
|
Sign up to set email alerts
|

A predictive account of how novelty influences declarative memory

Abstract: Highlights A single overarching theory of novelty and memory has been difficult to attain. Conflicting findings showing that novelty can enhance and impair memory in cases. Predictive coding framework is able to shed new light on different types of novelty. This has important consequences for the effect of novelty on declarative memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 157 publications
3
57
1
Order By: Relevance
“…While humans have the ability to retain and recall such information, potentially in isolation of the content that may have originally underpinned the time estimation [73], it is beyond the scope of our present modelling work to incorporate such influences. While of great interest, such work would require a much deeper understanding of the interaction of experience, language, and memory than we currently possess, though this is likely not outside the scope of an extended predictive processing approach [74].…”
Section: The Subjective Timescale Of Time Perception and Episodic Memorymentioning
confidence: 99%
“…While humans have the ability to retain and recall such information, potentially in isolation of the content that may have originally underpinned the time estimation [73], it is beyond the scope of our present modelling work to incorporate such influences. While of great interest, such work would require a much deeper understanding of the interaction of experience, language, and memory than we currently possess, though this is likely not outside the scope of an extended predictive processing approach [74].…”
Section: The Subjective Timescale Of Time Perception and Episodic Memorymentioning
confidence: 99%
“…When our 4 predictions are incorrect, we must update our mnemonic models of the world to support adaptive 5 behavior. Prediction error is a measure of the discrepancy between expectation and reality; this surprise signal is both evident in brain activity and related to learning success (1)(2)(3)(4)(5)(6). The brain dynamically reconstructs memories during recall, recreating and revising past experiences based on current information (7).…”
Section: Introductionmentioning
confidence: 99%
“…In Quent et al (2021 ), five types of novelty/surprise signals are outlined—item vs context novelty, item vs context surprise, and complete novelty, following the model of Henson and Gagnepain (2010 ). A model is being described of the interrelation between distributions of the subjective experience of novelty or surprise in terms of existence of prior memory and the current expectation.…”
Section: Learning Processes Revealed By Observing Eeg Activationsmentioning
confidence: 99%
“…By definition, the intensity of surprise is higher, than of novelty , due to the fact that in novelty no prior expectation is being formed as in surprise . In relation to surprise, Quent et al (2021) reported observed involvement of the hippocampus combined with increased motivation and exploration ( Kang et al, 2009 ; Gruber and Ranganath, 2019 )—psychological processes being largely involved in classroom learning.…”
Section: Learning Processes Revealed By Observing Eeg Activationsmentioning
confidence: 99%